(untitled) (SCIENCE TIME JOURNAL, 2026)
The interpretation of the human psyche in the works of Edgar Allan Poe and Abdurauf Fitrat explores profound psychological depths and social critique across their writings. Poe’s tales, such as "The Black Cat" and "The Tell-Tale Heart," delve into human perversity, guilt, hallucinations, and the boundaries of consciousness through psychological horror. Fitrat, in stories like "The Day of Judgment" and "The White Grave," satirically critiques superstitions, societal evils, and mental anguish with symbolic realism tied to everyday life. This theme unites explorations of humanity’s dark side with calls for social reform in literature.